Adjustment in Parents of Children Undergoing Stem Cell Transplantation - Lindwall, Jennifer J. (2014)
BACKGROUND: Pediatric stem cell transplant (SCT) is a demanding procedure for children and parents. Interventions to promote positive adjustment of parents in this setting are needed. METHOD: 171 patient/parent dyads from 4 sites received one of 3 interventions to reduce SCT-related distress: a child intervention with massage and humor therapy, an identical child intervention plus a parent intervention with massage and relaxation/imagery, or standard care. Parents completed weekly self-report measures of distress and positive affect during the acute phase of treatment (weeks −1 through +6), and measures of depression, posttraumatic stress (PTSD), and benefit-finding at baseline and week +24. RESULTS: No significant differences across treatment arms were observed on repeated measures of parental distress. There was a marginally significant effect of the child intervention on parental positive affect. Over time, parental distress decreased significantly and positive affect increased significantly in all groups. Similarly, there were no significant intervention effects on the global adjustment outcomes of depression, PTSD, and benefit finding. However, reports of depression and PTSD decreased significantly and reports of benefit-finding increased significantly from baseline to week +24 for all groups. CONCLUSION: Across all study arms, parent adjustment improved over time, suggesting that parents demonstrate a transient period of moderately elevated distress at the time of their child’s admission for transplant, followed by rapid improved to normative levels of adjustment. Similar to results previously reported for their children, these parents appear resilient to the challenges of transplant.